Changes in sulfate transport characteristics and protein composition of Anacystis nidulans R2 during sulfur deprivation. - Green, L S (1988)
Sulfur-starved cells of Anacystis nidulans have an increased capacity to take up sulfate. The apparent Vmax for sulfate uptake increased at least 10-fold after 24 h of sulfur deprivation, whereas the K1/2 remained unchanged at approximately 1.35 microM. The initial rate of sulfate uptake increased between 2 and 6 h after transfer of the cells to sulfur-free medium, in concert with elevated levels of three cytoplasmic membrane polypeptides with molecular masses of 43, 42, and 36 kilodaltons (kDa). The amounts of these polypeptides did not increase in response to nitrogen or phosphorus deprivation. A fourth cytoplasmic membrane polypeptide of 17 kDa did not appear until 24 h after transfer to sulfur-deficient medium. In the total soluble fraction, three polypeptides with masses of 36.5, 33.5, and 28.5 kDa increased dramatically in response to sulfur deprivation, but not in response to nitrogen or phosphorus deprivation. The specificity and abundance of these polypeptides indicate that they could play an important role in the response of A. nidulans to sulfur deprivation.